2015
DOI: 10.28998/rca.v12i1.1072
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos biológicos de Aphis craccivora Koch (Hemiptera: Aphididae) em cultivares de feijão-caupi Vigna unguiculata (L.) Walp

Abstract: <p>O pulgão preto, <em>Aphis craccivora </em>Koch (Hemiptera: Aphididae), é considerado uma importante praga do feijão-caupi, <em>Vigna unguiculata</em> (L.) Walp (Fabaceae), pois se alimenta da seiva e transmite viroses. Com o surgimento de novas cultivares do feijão-caupi torna-se necessário o estudo da resistência dessas plantas frente ao ataque das pragas. O trabalho objetivou avaliar os aspectos biológicos de <em>A. craccivora </em>sobre três cultivares do feijão-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
3
1
3
Order By: Relevance
“…Aphids on the MNCO4-792F-129 line had longer reproductive period (7.6 days) than those on the VITA 7 standard. Such values were lower than those found by Valente et al (2014), who reported a reproductive period of 4.20 days for cowpea aphid feeding on cultivar TVu 408 (a genotype regarded as aphid-resistant). On the other hand, De La Palva and Sepúlveda-Cano (2015) reported cowpea aphid reproductive periods ranged from 14.20 to 14.70 days on V. unguiculata genotypes.…”
Section: Resultscontrasting
confidence: 74%
See 3 more Smart Citations
“…Aphids on the MNCO4-792F-129 line had longer reproductive period (7.6 days) than those on the VITA 7 standard. Such values were lower than those found by Valente et al (2014), who reported a reproductive period of 4.20 days for cowpea aphid feeding on cultivar TVu 408 (a genotype regarded as aphid-resistant). On the other hand, De La Palva and Sepúlveda-Cano (2015) reported cowpea aphid reproductive periods ranged from 14.20 to 14.70 days on V. unguiculata genotypes.…”
Section: Resultscontrasting
confidence: 74%
“…Na linhagem MNCO4-792F-129, os insetos apresentaram maior período reprodutivo (7,6 dias), superior ao padrão VITA 7. Esses resultados foram inferiores aos encontrados por Valente et al (2014), quando o pulgão-preto ao se alimentar da cultivar TVu 408, considerado um genótipo resistente, apresentou um período reprodutivo de 4,20 dias. Por outro lado, o período reprodutivo do pulgão-preto variou de 14,20 a 14,70 dias sobre genótipos de V. unguiculata, em pesquisa realizada por De La Palva e Sepúlveda-Cano (2015).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Among the phytosanitary problems that can negatively influence cowpea productivity are attacks by Aphis craccivora Koch (Hemiptera: Aphididae), also known as cowpea aphid. This pest species causes great damage to the crop, as it can cause both direct effects (from sap sucking), and indirect ones, as the insect is a vector for several viruses that cause diseases for which there is no treatment (Moraes & Bleicher, 2007;Valente et al, 2014;Huynh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%